Architectonics of Game Spaces : The Spatial Logic of the Virtual and Its Meaning for the Real (2009)
Let us begin with something that might sound far-fetched: the children’s book King Nutcracker and Poor Reinhold, by Heinrich Hoffmann.2 In this story, a poor, sick boy is visited by an angel on Christmas Eve. The angel leads the boy away from his home, into a room with a small box full of wooden building blocks. Reinhold takes the blocks out of the box; after stacking them with the church in the center of his city, the blocks began to grow until they surrounded him—toy buildings that became “real.” In this fantastic city, Reinhold encounters a series of strange and unusual inhabitants, including a king who introduces the boy to his subjects.